2022
DOI: 10.3389/fpubh.2021.764681
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Misinformation Among Asian Americans During COVID-19

Abstract: Social media has been crucial for seeking and communicating COVID-19 information. However, social media has also promulgated misinformation, which is particularly concerning among Asian Americans who may rely on in-language information and utilize social media platforms to connect to Asia-based networks. There is limited literature examining social media use for COVID-19 information and the subsequent impact of misinformation on health behaviors among Asian Americans. This perspective reviews recent research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…In the Chinese focus group, for example, language-specific media and WeChat were mentioned as sources of information. Similarly, Chong et al found language-specific COVID-19 vaccine misinformation among Asian American subgroups on various social media platforms [ 39 ]. In addition, our findings indicate community-specific trusted sources of information that can be leveraged to disseminate HPV vaccine information to address hesitancy in racial/ethnic communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese focus group, for example, language-specific media and WeChat were mentioned as sources of information. Similarly, Chong et al found language-specific COVID-19 vaccine misinformation among Asian American subgroups on various social media platforms [ 39 ]. In addition, our findings indicate community-specific trusted sources of information that can be leveraged to disseminate HPV vaccine information to address hesitancy in racial/ethnic communities.…”
Section: Discussionmentioning
confidence: 99%
“…The deliberate inclusion of community advisory boards such as the NAC ensures the effectiveness of evidence-based interventions in public health emergencies and the increased uptake of COVID-19 testing and vaccination among underresourced and historically marginalized communities who may be distrustful of government and health institutions, 23 and vulnerable to COVID-19 misinformation. 24 …”
Section: Role Of Cbos In Bolstering Asian American Community Healthmentioning
confidence: 99%
“…In addition, misinformation is often spread between individuals through social media. Therefore, many researchers focus on misinformation, especially rumors spread on social media platforms (Chong et al, 2021;Vraga et al, 2020;Janmohamed et al, 2021). However, the definition of infodemic is "the proliferation of accurate information and inaccurate information during the pandemic" (Gruzd et al, 2021), which means we should be concerned with both misinformation and true information to manage infodemic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, misinformation is often spread between individuals through social media. Therefore, many researchers focus on misinformation, especially rumors spread on social media platforms (Chong et al. , 2021; Vraga et al.…”
Section: Introductionmentioning
confidence: 99%